GERAKAN SOSIAL DALAM PERSPEKTIF MAHATMA GANDHI - Kamaruddin Salim (Jurnal Ilmu dan Budaya, 2016)
Gandhi’s non-violance movement has basically been based on moral and religious force. The values that Gandhi promotes include fighting against use of hard force, of weapon; fighting for truth by way of self-purification. His movement is transformative in nature and puts humanity over varied basis of violence in terms culture, language and act. Gandhi’s major ideas are Ahimsa, Stayagrha, Swadeshi, Swaraj, and Sarvodaya—with which Gandhi struggles for the independence and de-colonizing his country, India.